Political Support for the Performance of Regionally-owned Enterprises: Case Study of PT Sulsel Citra Indonesia in South Sulawesi Province - Machmud, Yasir; Kambo, Gustiana A.; Irwan, Lukman (KnE Social Sciences, 2025)
The background of this research stems from a fundamental issue concerning how political power relations influence the performance of regionally-owned enterprises (BUMD), particularly in the case of PT Sulsel Citra Indonesia (SCI) in South Sulawesi Province. Preliminary findings indicate that the relationship between political elites and BUMDs is characterized by capital dependency, regulatory uncertainty, and the dominance of informal power networks. This study aims to analyze the forms and impacts of political support on BUMDs and to formulate an ideal model of power relations capable of enhancing their sustainable performance. This research employs a qualitative approach with an instrumental case study design. Data were collected through in-depth interviews with key informants from the provincial government, the Regional House of Representatives (DPRD), BUMD management, and relevant civil society actors. Thematic analysis was applied to trace the dynamics of actor relations and the tension between political power and business logic in regional enterprises. Each finding was interpreted using a theory-based reflective approach to reveal how power relations shape policy structures, decision-making processes, and the strategic direction of BUMDs. The results reveal that political support for BUMDs remains inconsistently institutionalized and is often exercised through patronage logic. Capital injection processes lack long-term regulatory planning, the appointment of directors tends to be politically driven, and the relationship between the executive, legislative, and BUMD management lacks a stable coordination forum. Consequently, this research formulates an ideal model of political support for BUMD performance, consisting of five key elements: (1) formal institutionalization as the main pillar, (2) limitation of political intervention, (3) managerial autonomy of BUMDs, (4) consolidation of a tripartite forum, and (5) a performance-based accountability system. This model is developed through the integration of empirical findings and theoretical reflections grounded in the Political Economy of Institutions (North), Public Choice Theory (Buchanan & Tullock), and Rent-Seeking Theory (Krueger). The theoretical implication of this study underscores the importance of institutionalizing power-business relations in the governance of public enterprises at the regional level, while the practical implication offers a strategic direction for regulatory reform and performance-based governance strengthening in BUMDs. This research also contributes to the academic discourse on local political dynamics within the institutional economic governance domain.